2019
DOI: 10.32479/ijeep.7578
|View full text |Cite
|
Sign up to set email alerts
|

Can a Green Tax Reform Entail Employment Double Dividend in European and Non-European Countries? A Survey of the Empirical Evidence

Abstract: This paper synthesises the simulation studies concerning green tax reform (GTR) and employment double dividend (EDD) in European and non-European countries. The studies included investigate the effect of GTR on employment. We compared the simulation results between European and non-European countries to understand the impact of study region and our findings are fivefold. First, the simulation results suggest that GTR-driven EDD is observed in both European and non-European countries, but the average effect on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…The primary dividend of GTR, which is reduction of CO 2 emissions, has already been reported time and again in the literature see [1,3,4,23,24]. The nexus between any kind of taxation on the use of fossil fuel, leading to a lower consumption of that and, therefore, lower emissions, is quite straightforward and undisputed.…”
Section: Simulation Scenariosmentioning
confidence: 95%
See 1 more Smart Citation
“…The primary dividend of GTR, which is reduction of CO 2 emissions, has already been reported time and again in the literature see [1,3,4,23,24]. The nexus between any kind of taxation on the use of fossil fuel, leading to a lower consumption of that and, therefore, lower emissions, is quite straightforward and undisputed.…”
Section: Simulation Scenariosmentioning
confidence: 95%
“…The use of environmental taxation as a policy instrument to address the negative externalities of economic activities (e.g., pollution) has been growing over the last several decades [1]. One of the key elements of evaluating the performance of such policies, however, is analysing the costs and benefits of the tax-based approach.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we need to compute the neutral reduction in the payroll tax rates that would offset the increased collection capacity of the eco-tax. This approach is the most common one for revenue recycling (Maxim and Zander, 2019). Notice that we select the level of fixed revenue in nominal terms since the government cannot foresee the endogenous change in the CPI.…”
Section: Simulationsmentioning
confidence: 99%
“…Besides these price-indexing adjustments, the government may choose to use its newly found eco-tax collections to reduce the public deficit (from the augmented tax burden) or, alternatively, it may choose to preserve the initial tax burden by recycling the eco-tax collections into lower tax rates in other tax categories. The meta-studies in Maxim and Zander (2019) and Maxim (2020) summarize the scope of these environmental tax recycling policies and their degree of success in different case studies for actually enacted or for just simulated eco-tax policies.…”
Section: Introductionmentioning
confidence: 99%
“…Such reform is also known as environmental tax reform (ETR) or green tax (or budget) reform (GTR). Maxim and Zander [18] analyzed the effects of substituting existing taxes by environmental taxes in European and non-European countries and found that an ETR has an average positive impact in employment for the European countries of 0.67% compared to the reference, but this number is highly dependent of the tax being substituted and varies from −0.15% for personal income tax (PIT) to 1.62% for VAT. Freire-González and Ho [19] use a CGE model to assess the effects of an ETR in Spain for three different levels of carbon taxes and four revenue recycling scenarios and discover a positive economic output in all scenarios for a tax level of €10/tCO 2 and some scenarios for a tax level of €20/tCO 2 .…”
Section: Introductionmentioning
confidence: 99%